Response of conifers to UV-B and climate in mountain areas - S.L. Bondarenko; D.A. Savchuk (Global Journal of Environmental Science and Management)
The present study was focused to examine the combined effects of climate and ultraviolet-B radiation on conifer tree-ring density. Statistical methods were employed to extract tree responses in annual ring density and to identify functional relationship in trees when the level of ultraviolet-B radiation changes regardless of climate variations. In this study, the consideration was given to the series of total ozone content (instead of ultraviolet-B), tree-ring density, and De Martonne aridity index. After the correlation analysis, all trees were divided into two groups: 1) Trees whose correlation between tree ring density and UV-B values in April is significantly positive; 2) Trees whose correlation between tree ring density and aridity index values in March-September is significantly negative. Then, tree-ring series for the Swiss Alps in each group were generalized and decomposed into separate components: long period trends, ultraviolet-B and climatic signals. For the ultraviolet-B-responsive tree group in the period 1932-1974, the correlation coefficient between the density and ultraviolet-B was 0.55 at p